Code clone detection using string based tree matching technique - Wahid, Norfaradilla (2008)
Code cloning have been an issue in these few years as the number of available web application and stand alone software increase nowadays. The major consequences of cloning is that it would risk the maintenance process as there are many duplicated codes in the systems that practically increase the complexity of the system. There are many code clone detection techniques that can be found nowadays which generally can be group into string based, token based, tree based and semantic based. The aim of this project is to find out the possibility of using a technique of ontology mapping technique to solve the problem, but we are not using the real ontology for the clone detection. It has been prove that there is the possibility as it manages to detect clone code. In this thesis the clone detection is using two layers of detection; i.e. structural similarity and string based similarity. The structural similarity is by using subgraph miner where it capable to get the similar subtree between different files. And then we extract all elements of that particular subtree and treat the elements as a string. Two strings from different files then applied with similarity metric to know whether it is a clone pair. From the experimental result, we found that the system is language independent but the result is good in precision but not so good recall. It is also capable to detect two main types of clone, i.e identical clones and similar clones.